Investigating The Impact of Tiktok Application Towards Speaking Proficency - Kurnia Sakti; Abdul Rohman; Widi Syahtia Pane (Inquest Journal, 2023)
Background:Individuals use spoken language when they speak, which is a sort of verbal communication. Speaking is animportant action in which a speaker presents his or her ideas and communicates with the audience. The messagedelivered by words or spoken language that provides meaning is referred to as verbal communication (Krauss,2012). Methodology:According to Creswell (2009:3), the term "research design" encompasses everything from study objectives andprocesses to particular data collection and analysis methodologies. As instructional materials, the authoremployed TikTok videos. The author applied the Experimental Method in this study, particularly for PreExperimental research. The "One Group Pretest-Posttest" design was employed in thisstudy. Findings:The data for this study were gatheredusing anoral test. The test was separated into two parts: pre-test and posttest. In the pre-test, students were given random questions thenthe students answer by speak up orally in the class. In the post-test, students were given the new random questions that different from pre-test then studentsanswer by speak up in front of class. Conclusion:Based on the result of the pre-test and post-test, it was found that the test was 29.94 by applying 0.05 level of significancewith 34 degree of freedom (df = 35 - 1 = 34) the author obtained t-table value 2.0322 from themean score of pre-test 168 and mean score of post-test 218. It shows that English Content from Tiktok videoshas significant effect in term of speaking proficiency. Originality:Speaking is a crucial tool in our daily lives for receiving messages and exchanging ideas. It is an interactiveaction in which the speaker generates, receives, and analyzes information in order to construct meaning. Asinstructional materials, the author employed TikTok videos to improve students’ speaking skills to this study.The author applied the experimental method in this study, particularly for pre-experimental research. The "onegroup pretest-posttest" design was employed in this study. The data for this study were gathered using an oraltest. The test was separated into two parts: the pre-test and the post-test. In the pre-test, students were givenrandom questions, to which they responded orally in class.In the post-test, students were given the new randomquestions that were different from the pre-test, and they answered them by speaking up in front of the class.Based on the result of the pre-test and post-test, it was found that the test was 29.94 by applying a 0.05 level ofsignificance with 34 degrees of freedom (df = 35 - 1 = 34). The author obtained a t-table value of 2.0322 from